Janda dan Resistensi Sosial dalam Lirik Lagu: Upaya Melawan Stigma Patriarki - Masyithah Maghfirah Rizam; Setya Yuwana; Darni; Suyatno; Anas Ahmadi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The stigma attached to women with widow status remains a strong social phenomenon in patriarchal societies, including in Madura. The identity of widows is often associated with negative connotations that hinder their freedom and rights in everyday social life. This study examines how the lyrics of modern Madurese songs represent social resistance against the stigma of widows through expressions of popular culture. Using a critical discourse analysis approach within the framework of social sciences, this research explores in depth how language in song lyrics constructs, maintains, or challenges existing social structures. The analysis focuses on two songs, Anyar Dedih Janda and Lanceng Abini Randha, which represent the voices of widowed women in confronting social stigma. The findings show that these songs not only reflect the lived experiences of widows but also function as advocacy tools in constructing alternative, more positive, and empowering narratives. Song lyrics become an important medium for promoting gender equality, redefining women’s identities, and shifting discriminatory social perceptions. This study highlights the crucial role of popular culture as a medium of resistance and social transformation against patriarchal norms in Madura.